Determinants of the development of a local currency bond market: the significance of macroeconomic stability - Matshego, Isaac (Graduate School of Business (GSB), 2019)
Bond market capitalisation in Sub-Saharan Africa is low even compared with the other developing economies. This dissertation thus examines the drivers of the development of local currency bond markets in 15 Sub-Saharan African economies over the period from 2003 to 2013, with a focus on the significance of macroeconomic stability proxied by exchange rate volatility. The empirical analysis focuses on government bond capitalisation, while the corporate bond market analysis focuses on seven of these economies for the period of 2004 to 2015. Possible explanatory factors are identified from the literature which attributes the development of local currency bond markets in developing economies to macroeconomic and institutional factors. The results of a dynamic panel data model show that macroeconomic instability is significant and negatively associated with local currency bond market capitalisation. In contrast, capital account openness is found to expand the investor base, for the low to lower-middle income economies in particular, while monetary credibility is positive and significant for bond market development irrespective of the monetary policy framework. Thus, this research suggests that the optimal set of policy options for local currency bond market development should encompass exchange rate stabilisation, capital account liberalisation, and monetary credibility.